MARITIME CULTURE AS A BASIS OF COMMUNITY RESILIENCE - Blajan Konradus (Jurnal Pluralis, 2024)
The existence of seas and rivers inherently also has a significant influence on the daily lives of coastal communities. Maritime culture has a very important role in preparing communities to face various challenges, especially in terms of economic, social and security resilience. This article discusses the importance of maritime culture as a basis for community resilience. In the economic realm, coasts and waters have the potential for abundant natural resources such as fish, coral reefs, gas and petroleum. Maritime culture also has a significant role in strengthening the social capacity of society through coastal life features such as unique ethnic, linguistic and cultural diversity. Maritime culture also becomes a link between communities in various coastal areas and facilitates the exchange of knowledge, skills and traditions between cultures and contributes to teaching the values ​​of cooperation, togetherness and mutual cooperation, which collectively strengthen the social resilience of communities. In terms of security, maritime culture is an important basis for building community resilience against threats related to waters. Finally, through a comprehensive analytical framework, the positive impacts of maritime culture in increasing economic, social and community security are also explained.